Mobility patterns and behaviours from a gender perspective in Alba Iulia metropolitan area, Romania - Adorean, E.; Kalakou, S.; Lynce, A.R. (Perspectives on gender in Romania, 2022)
Women’s mobility patterns differ from men’s regarding accessibility to the various transport services, transport safety, and personal security while travelling. These differences are explained by local transport supply, economic status, income, education level, perceptions or personal aspirations. By using GIS and Python coding, spatial analysis, descriptive statistics and statistical analysis, this chapter aims to analyse the mobility patterns and behaviours with an intersectional approach in Alba Iulia metropolitan area, highlighting the main differences between men and women on the most frequent journey without limitations associated with the COVID-19 pandemic. Results show that women in Alba Iulia metropolitan area travel shorter distances but spend more time travelling than men. Regarding car usage as drivers, approximately 2/3 are men, and 1/3 are women, with women more prone to use the car as a passenger. Additionally, women walk more than men and most likely use public transport services on their regular trips. In line with the literature, women stop more for shopping on the most frequent journey and men for work-related motives. Men are less satisfied with public transport services when compared to women. In contrast, when assessing private vehicle indicators, women are less satisfied than men in almost all aspects, namely park and ride locations, parking conditions, availability, safety, security, costs and congestion levels when using a private vehicle. A similar situation was observed regarding owned bicycles indicators, where women are less satisfied in almost all aspects analysed.